The Effect of Consumer Trust and Service Quality on Shopee Users Online Purchase Decisions - Harefa, Kelly; Gea, Elhan; Mendrofa, Yupiter; Bate’e, Maria Magdalena (Golden Ratio of Data in Summary, 2024)
This research is motivated by the development of the use of digital marketing in Indonesia, especially in the Nias Islands, which is currently running quite rapidly, which has directly given rise to new competition, this requires business actors to be more creative and innovative regarding the marketing changes that are currently occurring. This research aims to determine the influence of consumer trust and service quality on online purchasing decisions of Shopee users among students at the Faculty of Economics, Unversitas Nias, North Sumatera, Indonesia. This research is quantitative research with the research object at the Faculty of Economics, Unversitas Nias, North Sumatera, Indonesia. Data sources are taken from documentation, questionnaire results and observation results. Based on the results of the written analysis and discussion regarding the influence of Consumer Trust and Service Quality on Purchasing Decisions on the Shopee application, it can be concluded that Consumer Trust has a significant influence on Purchasing Decisions on the Shopee application which can be seen from the results of the t-test where Consumer Trust is 4,731 which is greater than t-estimated 2,645 and Service Quality with a t-value of 3,578 which is greater than t-estimated 2,645 and so H2 is accepted. Consumer Trust and Service Quality on Shopee Application Purchase Decisions. This can be proven by the statistical results of F-calculated of 19.008 which is greater than F-estimated of 3.12.